Analysis Of Outpatient Registration Efficiency Through The Implementation Of Electronic Medical Records At RSAU DR. M. Salamun - Asti Rahmi Fadjriani; Nadia Rizki Pratami (International Journal of Health Sciences, 2026)
This study aims to analyze the efficiency of outpatient registration services through the implementation of Electronic Medical Records (EMR) at RSAU dr. M. Salamun Hospital. A descriptive qualitative method was employed using the HOT-Fit framework, which comprises the Human, Organization, Technology, and Net Benefit dimensions. Data were collected through observation and interviews with outpatient registration staff. The results show that EMR implementation improves service efficiency by accelerating the registration process, facilitating patient data management, reducing queues, and supporting registration through the Mobile JKN application. In addition, EMR implementation reduces paper consumption and operational costs. However, several challenges remain, including unstable internet connectivity, disruptions to the registration and BPJS systems, and patients' lack of readiness in completing administrative requirements. Therefore, improvements in technological infrastructure, system development, staff training, and patient education are needed to optimize EMR implementation.